Mitigating the impact of soil salinity: recent developments and future strategies - Tedeschi, Anna; Schillaci, Martino; Balestrini, Raffaella (Italian journal of agronomy, 2023)
Soil salinity is among the major abiotic stresses that plants must face, mainly in arid and semiarid re-gions, and high salinity tolerance is an important agronomic trait to sustain food production. Agricul-tural soils are unstable and subject to changes in salinity level, and monitoring them at both the local and the regional scale is a relevant activity to adopt soil and water management strategies to decrease salt concentration in the root zone, thus minimizing impacts on plant growth and productivity. Addi-tionally, beneficial soil microorganisms such as arbuscular mycorrhizal fungi (AMF) and plant-growth promoting bacteria (PGPB), particularly when sourced in saline environments, can alleviate plant salinity stress by multiple mechanisms. In this review, some interventions aimed at reducing soil salinity will be discussed, as well as interventions aimed at reducing the vulnerability of crops to sa-line stress to obtain more tolerant plants. Highlights - Fast and reliable monitoring of soil status can help to promptly adopt strategies to decrease soil salin-ity and/or reduce crops vulnerability to salt. - Leaching, alternating fresh- and saline water for irrigation purpose and the use of efficient irrigation systems can be effective water management strategies against soil salinity. - Mulching and the use of amendments can improve soil status by decreasing its NaCl levels. - The rotation of halophyte and glycophyte plant species can allow NaCl sequestration while maintain-ing profitable yields. - Saline environments and plants adapted to such environments can be a valuable source of PGPB and AMF which can improve plant tolerance to salinity through multiple mechanisms.